(3GdaUOs - (3GdMSjf Hf YHO Gddg Hf GdMSf Hf Ydj Hf SjfG , CHh Ydj GdnHrdNqj Ke GdoHNGQqj GdeYQha HGHf SjfG, (B427 (3g`s
(3ChdgG (B:s
(3HYO GdHSedI QSGdI GdaUO , GdTjN GdQFjS , hYTQI CHhGH (B: (3GdHGH GdChd (B: (3ai MO GdaUO , GdHGH GdKGfi ai GdCZQGV GdebUhOI s
(3BNQgG (B:s
(3hERGOG GdfGS faYkG Hg GdJi Chai ef TQi SGFQ GdMeO ddg QH GdYGdejf s
(3Vef eLehY , JQJjHgG (B: (3ef U (B178 - (3U(B190s
(3fSNI KGfjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B241s
(3HQhcdeGf (B- (3GdLRA (B1 - (3U (B812 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA GdWH (B- (3bSe GdcJGH GdChd (B- (3U (B139 s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI NOGHNT HJfI (B(2559(4)) s
Keywords: (3GdWHs